PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. BNI SYARIAH CABANG UTAMA KOTA PEKANBARU - Fitri, Rahayu; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the study is to review Singer determine the effect Training ( X ) Against Employee Performance ( Y ) PT ON , BNI Syaraih Main Branch Pekanbaru. Singer Research method is quantitative hearts WITH using SPSS 21 , Where samples which are used Namely All employees IN. BNI Syariah Branch of Pekanbaru WITH respondents as many as 52 orangutans . Sampling technique is using census method . Research shows that the results of simultaneous testing Operating TIN Google Pages Of Finding The findings in the know T count ( 7572 ) > T table (2009 ) and Sig . ( 0,000 ) < 0.05 . This means that training variables significantly influence employee Against boarding costs .Keywords : Training , Employee Performance